2019
DOI: 10.1152/ajplung.00372.2018
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-30a as a candidate underlying sex-specific differences in neonatal hyperoxic lung injury: implications for BPD

Abstract: Premature male neonates are at a greater risk of developing bronchopulmonary dysplasia (BPD). The reasons underlying sexually dimorphic outcomes in premature neonates are not known. The role of miRNAs in mediating sex biases in BPD is understudied. Analysis of the pulmonary transcriptome revealed that a large percentage of angiogenesis-related differentially expressed genes are miR-30a targets. We tested the hypothesis that there is differential expression of miR-30a in vivo and in vitro in neonatal human pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 76 publications
1
29
0
Order By: Relevance
“…After hyperoxia exposure, miR-30a-3p and -5p levels increased significantly in female mice lungs on postnatal days 7 and 21 [27]. Similarly, in neonatal human pulmonary microvascular endothelial cells exposed to hyperoxia, samples obtained from females expressed significantly higher levels of miR-30a-3p and -5p compared to levels in male samples [27]. Altogether, there were significant decreases in miR-30a-3p and -5p levels, and increased mRNA and protein levels of DLL4 in human BPD lung samples.…”
Section: Consequences Of Mirnas Expression In the Developing Lungmentioning
confidence: 97%
See 2 more Smart Citations
“…After hyperoxia exposure, miR-30a-3p and -5p levels increased significantly in female mice lungs on postnatal days 7 and 21 [27]. Similarly, in neonatal human pulmonary microvascular endothelial cells exposed to hyperoxia, samples obtained from females expressed significantly higher levels of miR-30a-3p and -5p compared to levels in male samples [27]. Altogether, there were significant decreases in miR-30a-3p and -5p levels, and increased mRNA and protein levels of DLL4 in human BPD lung samples.…”
Section: Consequences Of Mirnas Expression In the Developing Lungmentioning
confidence: 97%
“…The administration of miR-876-3p mimic to postnatal day 14 mice exposed to hyperoxia restored alveolar structures and reduced neutrophilic inflammation [26]. After hyperoxia exposure, miR-30a-3p and -5p levels increased significantly in female mice lungs on postnatal days 7 and 21 [27]. Similarly, in neonatal human pulmonary microvascular endothelial cells exposed to hyperoxia, samples obtained from females expressed significantly higher levels of miR-30a-3p and -5p compared to levels in male samples [27].…”
Section: Consequences Of Mirnas Expression In the Developing Lungmentioning
confidence: 97%
See 1 more Smart Citation
“…We have previously shown that alveolarization and pulmonary angiogenesis is preserved in hyperoxia-exposed female neonatal mice compared to males [8]. The protective effect in females is accompanied by an increase in pulmonary miR-30a expression in females [9]. miR-30a has proangiogenic, anti-inflammatory, and antifibrotic effects in many diseases processes [1017], including those affecting the lung.…”
Section: Introductionmentioning
confidence: 99%
“…Donor sex alone has been found to influence phenotype in pulmonary microvascular endothelial cells. 268 , 269 Since hormones can heavily influence immune and lung function, it is important to account for the presence of hormones in media. 29 , 223 Phenol red-free media is recommended for such studies because phenol red can interact with estrogen receptors.…”
Section: Opportunities For Bioengineers To Study Respiratory Viral LImentioning
confidence: 99%